College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter R - Section R.4 - Polynomials - R.4 Assess Your Understanding - Page 47: 2



Work Step by Step

RECALL: $(a-b)(a+b) = a^2-b^2$ Use the formula above with $a=x^2$ and $b=4$ to obtain: $=(x^2)^2-4^2$ Note that $(x^2)^2 = x^{2\cdot2} = x^4$. Thus, the expression above is equivalent to: $=x^4-16$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.